2004
DOI: 10.1038/sj.npp.1300453
|View full text |Cite
|
Sign up to set email alerts
|

Acute Alcohol Effects on Neuronal and Attentional Processing: Striatal Reward System and Inhibitory Sensory Interactions under Acute Ethanol Challenge

Abstract: The acute influence of ethanol on cerebral activity induces complex psycho-physiological effects that are considerably more pronounced during acute ethanol influx than during maximal blood alcohol concentration (elimination phase). Despite the psychiatric and forensic relevance of these different ethanol effects, the underlying neuronal mechanisms are still unclear. In total, 20 male healthy volunteers were investigated each with three different experimental conditions in a randomized order using an intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 52 publications
4
36
0
4
Order By: Relevance
“…Activation in the left NAcc and left caudate increased relative to baseline signal in conjunction with subjective ratings of intoxication. These findings confirm PET data indicating increased glucose utilization during alcohol administration in striatum (Wang et al, 2000;Boileau et al, 2003;Schreckenberger et al, 2004), and support Koob's (1992) hypothesis that all drugs of abuse activate the striatum.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Activation in the left NAcc and left caudate increased relative to baseline signal in conjunction with subjective ratings of intoxication. These findings confirm PET data indicating increased glucose utilization during alcohol administration in striatum (Wang et al, 2000;Boileau et al, 2003;Schreckenberger et al, 2004), and support Koob's (1992) hypothesis that all drugs of abuse activate the striatum.…”
Section: Discussionsupporting
confidence: 80%
“…Similarly, functional magnetic resonance imaging (fMRI) studies have shown striatal activation in response to drugs of abuse such as cocaine (Breiter et al, 1997) and nicotine (Stein et al, 1998). Although there have not yet been fMRI studies of the action of alcohol on reward circuits, positron emission tomography (PET) studies demonstrate increased striatal glucose metabolism or blood flow in response to alcohol (Wang et al, 2000;Boileau et al, 2003;Schreckenberger et al, 2004). Accordingly, the mesocorticolimbic reward circuit is important in the development and maintenance of addiction (Koob et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…One potentially useful approach to investigate the in vivo effects of acute alcohol intoxication on cognitive performance is neuroimaging. Although many studies have used fMRI and PET imaging techniques to elucidate the neural effects of chronic alcoholism, only a few have addressed the effects of an acute dose of alcohol on cognitive performance (eg Schreckenberger et al, 2004;Vogel-Sprott et al, 2001). These neuroimaging studies have only assessed cognition in a single domain, such as attention or inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…These neuroimaging studies have only assessed cognition in a single domain, such as attention or inhibitory control. Schreckenberger et al (2004) may be the only investigators that aimed to test cognitive performance during rising and declining BACs, but their procedure of using intravenous alcohol resulted in such a rapid rise in BAC that tests could only be administered after peak BACs had occurred. Future neuroimaging research that administers a battery of computerized cognitive tasks, which are linked to a specific brain hemisphere, could explore possible differences between hemispheres in sensitivity to rising and declining BACs.…”
Section: Discussionmentioning
confidence: 99%
“…En la línea de estos datos, la mayoría de estudios comparativos entre consumidores y no consumidores han encontrado un peor rendimiento en consumidores abusivos en aquellas capacidades relacionadas con la memoria, la atención, las funciones ejecutivas y la fluidez verbal (Carballo, García, Jáuregui, & Sáez, 2009; Gross et al, 2011;Pitel et al, 2008;Schreckenberger et al, 2004). Concretamente, Crego et al (2009) encontraron diferencias electrofisiológicas a nivel cerebral entre consumidores y no consumidores.…”
Section: Introductionunclassified